Teaching Tacts, Listener Responding, and Effects on Intraverbals in Children with Autism (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
The effects of teaching methodologies based on Behavior Analysis are investigated over the learning ofintraverbals, which are usually impaired in autistic children. The purpose of this research was to assess theeffects of teaching tact and listener repertoires, by programming two different intervention packages for twopairs of autistic children, over the emergence of intraverbals consisting in listing category members. For twochildren from a tact condition, it was implemented the teaching of simple tacts, simple tacts with instructivefeedback and category tacts. For two children from a listener condition, it was implemented simple listenerresponses, responses with instructive feedback and category identification as listener. No intraverbalemergence effect was demonstrated and the direct teaching of this repertoire demanded the use of manyprompts (tact and echoic), producing increases in performance with variability for one participant anddependence of tact as prompt. Possibilities of methodological changes in the future are discussed.
Keywords: category intraverbals; tacts; listener responses; instructive feedback; autism